Ligninolytic Ability and Potential Biotechnology Applications of the South American Fungus Pleurotus laciniatocrenatus - Saparrat, Mario Carlos Nazareno (2005)
The extracellular ligninolytic enzyme system of Pleurotus laciniatocrenatus, grown under different culture conditions, was characterized and the ability of this strain to degrade different components of Eucalyptus globulus wood was determined. In shaken liquid cultures grown on a C-limited medium supplemented with yeast extract (0.1 %) and peptone (0.5 %), the fungus produced extracellular aryl-alcohol oxidase (Aao), laccase (Lac), manganese-dependent peroxidase (MnP) and manganese-independent peroxidase (MiP) activities, their maximum levels being, respectively, about 600, 50, 1360, and 920 pkat/mL. The supplementation of 1 mmol/L vanillic acid and 150 µmol/L CuSO4 produced an increase of Lac activity levels up to 4-fold and 68.3-fold, respectively. No significant differences were found in the levels of the other ligninolytic enzyme activities when compared to the basal medium. Solid-state fermentation cultures on E. globulus wood chips revealed Lac and MiP activities. These cultures showed degradative activity on lignin and lipophilic wood extractives.